Early preservation of effector functions followed by eventual T cell memory depletion: a model for the delayed onset of the effect of thiopurines. Issue 3 (2nd October 2008) - Ben-Horin, S; Goldstein, I; Fudim, E; Picard, O; Yerushalmi, Z; Barshack, I; Bank, I; Goldschmid, Y; Meir, S Bar; Mayer, L; Chowers, Y
Abstract : Objective: The onset of the effect of thiopurines is delayed for several months. The aim of this study was to investigate immune mechanisms for this delay. Methods: The effects of thiopurines on human peripheral blood T cells and on lamina propria lymphocytes were investigated for apoptosis induction by Annexin V/propidium iodide (PI) and for cytokine secretion by intracellular staining and ELISA assays. To investigate the mechanism of the effect of thiopurines in vivo, Balb/C mice were co-immunised with HEL/OVA (hen egg lysozyme/ovalbumin) antigens, and then repeatedly challenged by HEL only, while being treated by mercaptopurine or vehicle alone for either 4 or 20 weeks. The memory response of CD4+ splenocytes towards HEL/OVA was then determined by CFSE (carboxyfluorescein succinimidyl ester) dilution. Results: Thiopurines arrested the proliferation of stimulated T cells but did not enhance the apoptosis of either resting T cells or activated T cells until day 5 poststimulation. Despite the proliferation arrest, stimulated T cells successfully differentiated into effector cells, as evidenced by their capacity for proinflammatory cytokine secretion, potent adhesion and cytotoxicity. Prolonged mercaptopurine treatment of mice for 20 weeks selectively reduced the CD4+ memory response to a repeatedly encountered HEL antigen, but did not affect the T cell memory pool to the previously presented OVA antigen. A shorter, 4 weeks, treatment with mercaptopurine did not inhibit the memory response to either antigen. Conclusions: T cells arrested from cycling by thiopurines can still differentiate into potent effector cells capable of propagating the inflammatory process. Thiopurine treatment results in depletion of antigen-specific memory T cells, but this effect is dependent upon repeated encounters with the antigen over a prolonged time course.